Types and abundance of zooplankton in the Tajwid Lake, Langgam Sub-District, Pelalawan District, Riau Province - Aspi Mardhana; Tengku Dahril; Madju Siagian (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
Tajwid Lake is an oxbow lake that receives water from the Kampar Riverduring rainy season. To understand the types and abundance of zooplanktonpresent in that lake, a study has been conducted in February 2016. There were 3stations, Station 1 is in the inlet, Station 2 is in the middle of the lake and Station3 is in the outlet. Samplings were conducted 3 times, once/week. Results shownthat there are 20 species of zooplankton present in the lake. They were classifiedinto four classes, namely: 3 Rotifer species, 4 Crustacean species, 2 Sarcodinaspecies, 2 Cladocera species, and 2 Monogononta species, 1 Branchiopodaspecies, 1 Ciliata species, 1 Copepoda species, 1 Insecta species, 1 Phyllopodaspecies, 1 Maxillopoda species, 1 Granulureticulosa species. The average ofzooplankton abundance was around 1,582-3,990 ind/L, species diversity index(H’) was 3.95-4.10, uniformity index (E) was 1.15-1.25 and dominance index (C)was 0.08-0.07, indicated there is not a dominant species in the lake. While thewater quality parameters were as follows: temperature 290C, transparency 33-51cm, depth 600-1,200 cm, pH 5, DO 4.9-6 mg/L, and CO2 8.2-8.6 mg/L. Thevalues of water quality parameters indicate that the aquatic environment in theTajwid lake is good and is able to support the life of aquatic organisms, especiallyzooplankton.Keyword : Zooplankton, Tajwid Lake, Oxbow Lake.